The ethyl acetate fraction of a methanolic extract of unripe noni (Morinda citrifolia Linn.) fruit exhibits a biphasic effect on the dopaminergic system in mice - Pandy, Vijayapandi (Exp Anim, 2017)
In earlier ex vivo studies, we reported the biphasic effect of a methanolic extract of unripe Morinda citrifolia fruit (MMC) on dopamine-induced contractility in isolated rat vas deferens preparations. The present in vivo study was designed and undertaken to further explore our earlier ex vivo findings. This study examined the effect of the ethyl acetate fraction of a methanolic extract of unripe Morinda citrifolia Linn. fruit (EA-MMC; 5–100 mg/kg, p.o.) on the dopaminergic system using mouse models of apomorphine-induced climbing time and climbing behavior, methamphetamine-induced stereotypy (sniffing, biting, gnawing, and licking) and haloperidol-induced catalepsy using the bar test. Acute treatment with EA-MMC at a low dose (25 mg/kg, p.o.) significantly attenuated the apomorphine-induced climbing time and climbing behavior in mice. Similarly, EA-MMC (5 and 10 mg/kg, p.o.) significantly inhibited methamphetamine-induced stereotyped behavior in mice. These results demonstrated that the antidopaminergic effect of EA-MMC was observed at relatively lower doses (<25 mg/kg, p.o.). On the other hand, EA-MMC showed dopaminergic agonistic activity at a high dose (3,000 mg/kg, p.o.), which was evident from alleviation of haloperidol (a dopamine D(2) blocker)-induced catalepsy in mice. Therefore, it is concluded that EA-MMC might possess a biphasic effect on the dopaminergic system, i.e., an antagonistic effect at lower doses (<25 mg/kg, p.o.) and an agonistic effect at higher doses (>1,000 mg/kg, p.o.). However, further receptor-ligand binding assays are necessary to confirm the biphasic effects of M. citrifolia fruit on the dopaminergic system.